PS 06-16 PREVALENCE AND CLINICAL FEATURES OF PREDIABETES IN PATIENTS WITH HYPERTENSION. (September 2016) - Park, Chang; Park, Sung; Park, Eun; Choi, Ja; Lee, Sun; Choi, Chul; Na, Jino; Kim, Jin; Rha, Seung; Seo, Hong; Oh, Dong
Abstract : Objective: Although prediabetes and hypertension are major components of metabolic syndrome, there is no reported data on the prevalence of prediabetes (FBS 100–125 mg/dL or HbA1c 5.7–6, 4%) in hypertensive patients. We evaluated the prevalence and characteristics of prediabetes among hypertensive patients treated at primary clinics in Korea. Design and Method: Anthropometric and hemodynamic data and a variety of laboratory tests using serum and urine were obtained for 3109 patients who participated in the Wonder study which is a nation-wide, multi-centered, cross-sectional study. Risk factors and comorbidities according to diabetes status tertiles (normal, prediabetes and diabetes) were identified using multilevel logistic regression models. Results: The overall prevalence of normal, prediabetes and diabetes in patients with hypertension was 21.8%, 48.7and 29.5%, respectively. Smoking is significantly less in prediabetes and diabetic patients compared to normal glucose hypertensive subject. However, risk factors (high waist circumference and serum triglycerides, and low serum high-density lipoprotein), and subclinical organ damages such as LVH and microalbuminuria, and coronary artery disease, CKD and peripheral arterial disease were significantly increased as increasing diabetes status tertiles. Conclusions: The prevalence of prediabetic state in hypertension patients was 48.7%. Epidemiological factors of the prediabetes in hypertension patients showed higher CV risk factors and CV comorbidities, Almost half adults in Korean hypertensive patients was found to have prediabetes. We should have action to prevent prediabetes to be diabetes through better detection, awareness, prevention and treatment.